Confronting the challenge of youth violence in society : defining a multi-sectoral approach : remarks - Ramdin, Albert R. (OAS [Washington]US, 2009)
Notes the ill effects of crime and youth violence on the economies of the Caribbean. Highlights two forms of assistance provided by the OAS to Member States. Suggests that policies for tackling the sources of youth crime and violence must form part of the overall development and democracy framework.